Double-blind evaluation of clonazepam on periodic leg movements in sleep. - Peled, R (1987)
Treatment with clonazepam was studied in a group of 20 patients suffering from periodic movements in sleep, in a double-blind parallel group design. Eleven complained of excessive daytime sleepiness, and nine complained of insomnia. Ten patients received clonazepam, and 10 received placebo, over a period of 1 month. Clonazepam (0.5-2 mg per night) proved to be an effective treatment of periodic movements in sleep. Polysomnographic recordings demonstrated a significant decrease in the number of leg movements and a significant improvement in sleep parameters in the clonazepam group as compared with placebo. Subjective responses to treatment corroborated the sleep laboratory findings.